Comparison of Optimal Power Flow Formulations in Active Distribution Grids - Mylonas, Costas; Karagiannopoulos, Stavros; Aristidou, Petros; Shchetinin, Dmitry; Hug, Gabriela (My University, 2020)
Active Distribution Networks (DNs) are expected to host an increasing number of Distributed Generators (DGs) and other Distributed Energy Resources (DERs), offering new flexible sources and enabling the provision of ancillary services to system operators. Centralized DER controls that use Optimal Power Flow (OPF) methods necessitate tractable and scalable computational tools that can handle large DNs with satisfactory performance. In this paper, we compare an iterative OPF method against the standard exact AC OPF calculations in terms of the computational effort and solution quality. Furthermore, we highlight the suitability of the selected formulation to offer voltage support (VS) as an ancillary service to the transmission network. The results are demonstrated using a joint medium and low voltage grid, and show that tractable OPF formulations can unlock financial business cases for DNs that can actively participate in VS schemes.
Keywords: Backward forward sweep power flow; DSO; Centralized control; Voltage support; Active distribution networks; OPF; TSO; ancillary services